Development of a strategically driven production facilities management (PFM) framework - Liu, Wei-Chung (Cranfield University, 2000)
This thesis presents the results of a programme of research into the development and evaluation of a strategically driven Production Facilities Management (PFM) framework. PFM is the activity of managing production facilities to fully realise the corporate strategic objectives of a manufacturing organisation. Companies with strategies tend to be more successful than companies without them. The concept of manufacturing strategy is an approach to enhance the consistency between the manufacturing function and the direction of the organisation. Consequentially, PFM is the means to ensure these strategic requirements can be fully realised from the facilities management viewpoint. Through the literature review, it was seen that there is a lack of a link between manufacturing strategy and the management of production facilities. From questionnaire surveys and interviews at companies in the manufacturing sector, it was found that the issue of linking facilities management with corporate strategy has been ignored. Therefore, this programme of research not only investigates the context and contents in formulating an appropriate manufacturing strategy in a manufacturing environment but also reviews the most popular methods in relation to maintenance management and performance assessment of the facilities. This programme describes the development of a strategically driven, step-by-step approach that helps a company to capture the strategic requirements of the manufacturing function, measure the performance of existing production facilities and supports the decision-making analysis tasks. The primary contribution of the work presented in this thesis was the development of an implementation framework and an associated implementation workbook which comprise a set of stages and implementation sections that a user can use to carry out the process of capturing the strategic requirements and realise them with support from an appropriate PFM framework and a systematic, step-by-step implementation process.